Acceptability of Postpartum No-Cost LARC Among Women Using Emergency Medicaid for Labor and Delivery [19F]. (May 2018) - Dempsey, Angela; Billings, Debbie; Mattison, Amy; Burgis, Judith; Tyson, Adam
Abstract : INTRODUCTION: In 2012, South Carolina (SC) instituted a Medicaid policy allowing full reimbursement for inpatient post-partum long acting reversible contraceptives (LARC) and related services; however, the policy does not apply when delivery costs are covered by Emergency Medicaid. This study evaluated the acceptability of inpatient postpartum no-cost LARC for women with Emergency Medicaid coverage. METHODS: This cross-sectional study enrolled participants following delivery in three teaching hospitals in SC between November 2016 and May 2017. Eligible women were at least 18 years old and qualified for Emergency Medicaid coverage. Data were collected through patient interviews and chart abstraction. Each site provided LARC at no cost regardless of study enrollment. RESULTS: Among the 220 women enrolled, 89 women (40%) left with either the implant (n=57) or an IUD (n=32). Among those women, 79% were "very satisfied" with the insertion. When comparing pre-delivery documented contraception plans with method recorded at discharge, we found an increase in those choosing implant (pre= 18%, postpartum=26%) and a decrease in no method (pre= 26%, postpartum=15%) and IUD (pre=17%, postpartum= 15%, ). Contraceptive counseling was recorded in most inpatient records (81%) and prenatal records (76%). Few participants reported receiving the information they needed about the IUD (36%) or implant (38%). Though 89% of participants planned to breastfeed, only 70% and 6% received information about breastfeeding while using implants and IUDs, respectively. CONCLUSION: LARC methods were commonly selected postpartum among this population. Despite counseling documented by providers, patients receive insufficient information about specific LARC methods and their use while also breastfeeding.